INDIKATOR MONITORING DAN EVALUASI TARGET SDGs YANG RESPONSIFE (SIMULASI DATA SCORSING / TOOLS BAR DENGAN METODE ARTI) - Erry Jayanti (Jurnal Real Riset, 2023)
In supporting sustainable development in Indonesia, the INFID TEAM prepared a Regional Action Plan (RAD) of the 2023-2030 Sustainable Development Goals (TPB/SDGs). Achieving the SDGs can only be successful if all regions in Indonesia, totaling 530 urban districts, make efforts to implement all or part of the goals and targets of the SDGs. For this reason, it is necessary to carry out a simulation in order to obtain the right indicators for monitoring and evaluating the SDGs using the Scoring Tools Bars data using the Responsive, Transformative and Inclusive (ARTI) Score Analysis method. The purpose of this study is to obtain an accurate description or mapping in order to find and develop SDGs indicators that are in accordance with the direction of the future situation. The method in this study is the literature review approach and the desk review method, namely the method of collecting data and information through examination and analysis of data and information using secondary data. The results in this study indicate that the simulation of the coherent SDGs Score Card can be standardized as a recommendation for the preparation of valid SDGs indicators, because the reliability of the data has been tested which shows that it is responsive to the conditions of residents such as welfare and health data considered factual as well as scores of economic growth and people's income are considered factual and responsibility as obtained from survey results and baseline data. The SDGs scoring card is also able to provide the right decisions for further development.Keywords : TPB- SDGs, Scord Card,  ARTI